The Influence of Teaching Using Poem on Students’ Vocabulary Mastery: A Systematic Review - Kabinawa, Putu Kunang; Santosa, Made Hery (Universitas PGRI Adi Buana Surabaya, 2024)
This study uses a systematic review of fifteen studies published between 2016 until 2024 to find out the impact of poetry as a teaching medium on EFL students' vocabulary mastery. The findings show that poetry's rhythmic and emotionally engaging language improves learning enjoyment and helps in memorizing new words. Poetry improves student understanding and usage of new words by offering context and promoting creative expression. Poetry also increases cultural and language awareness, which is necessary for developing empathy and communication skills, as well as cognitive benefits including improved critical thinking and problem-solving ability. The study suggests incorporating poetry into EFL courses, educating teachers, and developing assessment tools to assess its effect on vocabulary learning and student engagement. Future research is needed to look at the long-term effects of poetry-based teaching and its impact on varied student populations, in order to provide comprehensive insights for teachers and curriculum developers.